2013
DOI: 10.1021/bi401345b
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Avidity To Improve Antifreeze Protein Activity: A Type III Antifreeze Protein Trimer Exhibits Increased Thermal Hysteresis Activity

Abstract: Antifreeze proteins (AFPs) are ice growth inhibitors that allow the survival of several species living at temperatures colder than the freezing point of their bodily fluids. AFP activity is commonly defined in terms of thermal hysteresis, which is the difference observed for the solution freezing and melting temperatures. Increasing the thermal hysteresis activity of these proteins, particularly at low concentrations, is of great interest because of their wide range of potential applications. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…As the number of accessible ice binding sites, or avidity, increases on an AFP, its efficiency at binding with ice and TH activity increase 32,33,44 . Hence, the cooperative effect we demonstrated between the two domains of IBPv may be a result of increasing avidity on each protein molecule.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of accessible ice binding sites, or avidity, increases on an AFP, its efficiency at binding with ice and TH activity increase 32,33,44 . Hence, the cooperative effect we demonstrated between the two domains of IBPv may be a result of increasing avidity on each protein molecule.…”
Section: Discussionmentioning
confidence: 99%
“… 66 , 78 Maximal TH activities measured by cryoscopy range from 0.1–0.5 °C in apoplastic extracts from overwintering plants 4 , 61 and ∼2 °C for 30–40 g L –1 protein in fish serum 21 , 74 to ∼2 to 13 °C for 10-times lower concentrations in insect hemolymph. 54 TH activity can be improved upon addition of (sub)molar concentrations of small molecular solutes 79 and ions, 20 , 80 conjugation 81 to or complexation 82 with potentiating proteins 82 or other ice-binding proteins 81 and polymers, 83 , 84 and IBS enlargement. 85 However, salts like sodium borate can also inactivate AFGPs.…”
Section: Ibp Activitymentioning
confidence: 99%
“…In both cases, connecting two almost homologous domains increases the TH value cooperatively compared with their monomeric AFPs [139,209]. Studies from the laboratories of Tsuda, Davies, and Holland have demonstrated that the multimerization of native type III AFP can increase TH activity [210,211,212]. Recently, Steven et al claimed the dendrimer-like AFPs showed higher TH values [213], and Phippen et al demonstrated 12 AFP-fused protein cage nanoparticles that increased the TH value to more than 50-fold that of monomeric AFP [214].…”
Section: Conclusion and Perspectivementioning
confidence: 99%